PENGARUH PELATIHAN DAN PENGEMBANGAN SDM TERHADAP PRODUKTIVITAS KERJA GURU KEJURUAN DI SMKN 2 BANDAR LAMPUNG - Windi Widianti; Rahmat Hidayat; Eti Hadiati; Junaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Training and human resource (HR) development play a crucial role in enhancing workplace productivity, particularly among teachers. Competent educators can significantly influence the quality of teaching and student learning outcomes. At SMK Negeri 2 Bandar Lampung, vocational teacher training is conducted regularly; however, it often serves as a mere formality and fails to effectively improve teacher competencies. Therefore, evaluating the effectiveness of these training programs is essential to ensure that educational objectives are successfully achieved. This study aims to examine the impact of training and HR development on teacher productivity and to identify the factors that influence training quality at SMKN 2 Bandar Lampung. A quantitative research approach was employed, using surveys administered to vocational teachers. The findings reveal a significant relationship between training and increased teacher productivity. These results underscore the importance of continuous, well-structured, and relevant training programs in enhancing teacher performance, which ultimately contributes to improved educational quality and student achievement. This research offers valuable insights for the development of more effective training policies within the context of vocational education.